A Complete H.264 Motion Estimation Architecture - Siqueira, Hadley; Lopes, Alba; Marinho, Victor; Corrêa, Edgard (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
H.264 is the state of the art regarding video compression standards. One of its main compression tools is motion estimation with fractional motion support. Although it is the tool that offers the best gain on data compression, it also requires a lot of computation power. The motion estimation also requires a very high bandwidth with the external memory to perform its operations. In this paper, we present a complete motion estimation architecture that reduces memory bandwidth and is capable of performing full, half and quarter pixel precision refinement. Results show that the proposed architecture can achieve a display rate of 30 frames per second for HD 720p resolution with an operation frequency of 102 MHz.